Kansas academic librarian perceptions of information literacy professional development needs - Starkey, Alysia (Kansas State University, 2010)
The purpose of this study was to assess the professional development needs of academic instruction librarians required to improve information literacy instructional effectiveness in higher education institutions within the state of Kansas. The population in this correlational study was the 84 academic librarians with instruction duties at Kansas two-year colleges, four-year colleges, and universities. The majority of the population included administrators, staff, and specialized librarians. Most of the participants held a faculty rank, were between the ages of 41 and 55, and had served as academic librarians for less than fifteen years. Data was collected through twelve closed-ended and twelve open-ended questions on an electronic survey. The data was used to answer the primary research question of this study: “What professional development opportunities are needed in order to improve information literacy instructional effectiveness?” Three sub-questions were included in order to identify professional development needs on the various means by which information literacy is delivered, the content areas addressed during information literacy instructional sessions, and the assessment practices employed to determine the effectiveness of information literacy instruction. Data analyses for the quantitative measures of the study were conducted through the use of frequency distributions (in order to identify professional development needs of the total population) and chi-square tests (in order to identify professional development needs of the individual sub-populations). Due to the low number of answers to open-ended questions, responses to these questions were analyzed for codes and developed into categories. Analyses of the data indicated that the sub-populations shared a preference for library instruction delivered via face-to-face means; all institutions represented in this study offered considerably more instruction than what was required by their parent institution; Kansas academic instruction librarians addressed a wide variety of services, resources, search techniques, and information literacy skills during information literacy instructional sessions; and Kansas academic instruction librarians were cognizant of ensuring instruction practices were designed to include content that met the guiding information literacy standards as defined by the American Library Association. The study found Kansas academic librarians with instruction as a function of their job duties would benefit from professional development opportunities designed to develop proficiency in teaching skills, instructional design skills, assessment and evaluation skills, information literacy integration skills, and presentation skills.
Keywords: Information literacy; Library instruction; Continuing education; Higher education; Education, Higher (0745); Education, Teacher Training (0530); Library Science (0399)